Association of Obesity and C-Reactive Protein with Coronary Artery Disease (Bangladesh Heart Journal, 2021)
Background: Obesity is now becoming a global epidemic. It is most of the times associated with hypertension, diabetes mellitus (DM), metabolic syndrome and dyslipidemia which are known risk factors for coronary artery disease (CAD). Coronary arteriosclerosis comprises a series of inflammatory responses at cellular and molecular level, whose reactions are stronger in obese patients. The objective of this study was to observe the association of obesity and raised inflammatory markers with CAD.Method: This cross-sectional study was carried out in the Department of Cardiology, Dhaka Medical College Hospital, Dhaka, Bangladesh, involving 668 patients of ischemic heart disease who underwent coronary angiography (CAG) from January 2017 to December 2017. Obesity was defined as body-mass index (BMI) ≥30.0 kg/m2. C-reactive protein (CRP) was measured as the inflammatory marker, and was considered as high if >10 mg/L. CAD was classified on the basis of CAG findings: insignificant if stenosis is 10 mg/L), DM, and high HbA1c (≥6.5%) were found significant predictors of severe CAD (p